KEBIJAKAN PUBLIK DALAM UJIAN (KAJIAN HUKUM DALAM PROYEK PUSAT OLAH RAGA HAMBALANG) - Florentinus Sudiran (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The aim of this research is to know the process of the supremacy of law in Indonesia by the commission of corruption destruction (KPK). The method of it is library research by secondary data from the two local news-papers namely Kaltim Post and Tribun Kaltim. The location of it is in Samarinda. The duration of it is three months from August to December 2013 which correlated with the commission concerned especially the two persons who were arrested by the commission. Two of them deny involving in the corruption of Hambalang. The two persons namely Andi Malarangeng and Anas Urbningsrum are split in continuing the law process because they do not acknowledge corrupting. Andi said that he did not corrupt either he himself or his brother Cull Malarangeng. Meanwhile Anas denies being corruptor on Hambalang such as gratification of a car because he never has any business with any project. Then the writer will take the data from the newspapers. The method of this research is qualitative one .The result of it is that the two persons concerned are strongly accused to corrupt. The result of the research is that in the court of corruption action (tipikor) there are some proofs told that they were involved the corruption of Hambalang.